Feasibility Study of Bitumen Asphalt (Asbuton) Plant in Mass-Production Scale - Rochelle Trixie Silalahi; Muhammad Saiful Hakim; Imam Baihaqi; Puti Sinansari; Anandita Ade Putri (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Purpose – This study aims to assess the operational and financial feasibility of mass-producing Asbuton (Buton natural asphalt) as a sustainable alternative material for road construction in Indonesia. Methodology – This study adopts a feasibility study framework integrating operational and financial analyses. The operational assessment covers plant location selection, plant capacity determination, facility layout planning, and production process evaluation. Financial feasibility is analyzed through projected cash flow estimation based on capital and operational expenditures, employing investment appraisal indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). A sensitivity analysis is further conducted to evaluate the impact of price variations on project viability. Findings – The results indicate that the proposed Asbuton production plant is both operationally and financially feasible. The financial indicators demonstrate satisfactory investment performance, while sensitivity analysis shows that the project remains viable under reasonable fluctuations in key economic variables. Technological advancement and efficient operational planning play a critical role in improving cost efficiency and competitiveness. Originality – This study offers a comprehensive feasibility assessment by integrating operational design, financial evaluation, and sensitivity analysis for large-scale Asbuton production. It contributes empirical evidence to the limited literature on natural asphalt commercialization in emerging economies, particularly Indonesia.